2014
DOI: 10.1155/2014/690529
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Dense Granular Protein (GRA5) for Detection of Human Toxoplasmosis by Western Blot

Abstract: Toxoplasma gondii infects all warm-blooded animals, including humans, causing serious public health problems and great economic loss for the food industry. Commonly used serological tests require costly and hazardous preparation of whole Toxoplasma lysate antigens from tachyzoites. Here, we have evaluated an alternative method for antigen production, which involved a prokaryotic expression system. Specifically, we expressed T. gondii dense granular protein-5 (GRA5) in Escherichia coli and isolated it by affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…After removing the transmembrane region, the gene fragment encoding amino acids 24-194 was used to express the protein, and a speci c 27-kDa band was observed on SDS-PAGE. Our result was similar to that of Babaie et al [11], who designed and expressed a recombinant protein from the GRA8 gene fragment corresponding to amino acids 23-169. However, a difference in size between the apparent band and the calculated molecular weight of TgGRA8 (22.62 kDa) was observed in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…After removing the transmembrane region, the gene fragment encoding amino acids 24-194 was used to express the protein, and a speci c 27-kDa band was observed on SDS-PAGE. Our result was similar to that of Babaie et al [11], who designed and expressed a recombinant protein from the GRA8 gene fragment corresponding to amino acids 23-169. However, a difference in size between the apparent band and the calculated molecular weight of TgGRA8 (22.62 kDa) was observed in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Dense granule antigens (GRAs) of T. gondii are secreted in the parasitophorous vacuole (PV), and they are involved in survival and virulence of the parasite [9]. Several studies demonstrated the diagnostic potential of numerous GRAs such as GRA2 [10], GRA5 [11], GRA6 [12], and GRA7 [13,14]. GRA8 is a 38-kDa praline-rich (24%) protein that is released from PVs shortly after invasion.…”
Section: Introductionmentioning
confidence: 99%
“…After removing the transmembrane region, the gene fragment encoding amino acids 24-217 was used to express the protein, and a speci c 27-kDa band was observed on SDS-PAGE. Our result was similar to that of Babaie et al [12], who designed and expressed a recombinant protein from the GRA8 gene fragment corresponding to amino acids 23-169. However, a difference in size between the apparent band and the calculated molecular weight of TgGRA8 (23.71 kDa) was observed in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Dense granule antigens (GRAs) of T. gondii are secreted in the parasitophorous vacuole (PV), and they are involved in survival and virulence of the parasite [10]. Several studies demonstrated the diagnostic potential of numerous GRAs such as GRA2 [11], GRA5 [12], GRA6 [13], and GRA7 [14,15]. GRA8 is a 38-kDa praline-rich (24%) protein that is released from PVs shortly after invasion.…”
Section: Introductionmentioning
confidence: 99%
“…The potential ability of specific T. gondii recombinant antigen to identify the clinical phases of the disease was extensively studied, in the attempts to discriminate acute from chronic infection. The performance of recombinant antigen seems to be sensitive enough and promising in differentiating acute versus chronic infection [35,38]. Although there is no clear definition of either chronic or acute infection, identification of recently acquired infection normally relies on the detection of specific IgM in patients serum;…”
Section: Recombinant Antigensmentioning
confidence: 99%